Improving the Reading Comprehension Skills of Fifth-Grade Students at UPT SD 068007 Medan Tuntungan through the Direct Instruction Learning Model in Indonesian Language Instruction - Juliana Panjaitan; Pebryanti Tanjung; Esy Arthamevia; Feronika Sipayung; Difla Sipayung (Darul Yasin Al Sys, 2026)
Reading comprehension is a fundamental language skill that enables elementary school students to understand learning materials across subject areas; however, the reading comprehension achievement of fifth-grade students at UPT SD Negeri 068007 Medan Tuntungan remained relatively low. This study aimed to improve students’ reading comprehension skills through the implementation of the Direct Instruction model in Indonesian language learning. Classroom action research based on the Kemmis and McTaggart model was conducted in two cycles, each comprising planning, action, observation, and reflection. The participants were 23 fifth-grade students. Data were collected through observations, tests, interviews, and documentation and analyzed using qualitative and quantitative descriptive techniques. The findings demonstrated progressive improvements in students’ reading comprehension achievement across the research stages. At the preliminary stage, only five students (21.7%) achieved the Minimum Mastery Criterion, with a mean score of 52.17. Following the implementation of Direct Instruction in Cycle I, mastery increased to 39.1%, with a mean score of 62.61. In Cycle II, mastery further increased to 82.6%, accompanied by a mean score of 83.50. Teacher activity improved from 66% in Cycle I to 86% in Cycle II, while student activity increased from 58% to 80%. These findings indicate that the Direct Instruction model effectively improves reading comprehension by providing structured explanations, guided practice, and systematic learning activities. The study contributes practical evidence supporting the use of explicit and sequential instruction to enhance reading comprehension achievement and classroom engagement among elementary school students.